Constitutional Design of State Policy as Guidelines on Indonesia’s Presidential System Development Plan - M. Wildan Humaidi; Inna Soffika Rahmadanti (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
After the 1945 Constitution amendment, there is a need to improve and rearrange Indonesia’s state administration system. That the State Policy Guidelines (GBHN), as a product of the People’s Consultative Assembly (MPR) Decree, is annulled has the national development planning and process lost their direction and had unclear goals. Therefore, this research elaborated further on the necessity of realizing state policy’s main points as guidance for development planning and offering ideas for the format of the presidential system design regulation following the Indonesia’s post-reform constitution. This conceptual research used a comparative constitutional approach to find an appropriate and applicable model in Indonesia context. The existing models were explored, mapped, and formulated for the most feasible model suitable for Indonesia. This study found the need for the 1945 Constitution amendment agenda to accommodate state direction as the Directive Principles of State Policy (DPSP) concept in the 1945 Constitution of Republic of Indonesia, and for President and the Constitutional Court to support the accountability and enforcement of state laws in governmental administration.